(untitled) (Baghdad Science Journal, 2006)
In this study, measuring effectiveness Alauriz in some seeds powder and found that the seeds of-sophistication sex had the highest effective enzymatic reach 353 units / gProtein and Alkabbatah study enzyme extract under different storage conditions and Altaj showed that the enzyme loses Thbatih and whether Mrkbhetwan adding Alklasrin concentration of 10% for the systematic solution